2011
DOI: 10.1111/j.1582-4934.2010.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated miR‐331–5p and miR‐27a are associated with chemotherapy resistance and relapse in leukaemia

Abstract: Multidrug resistance (MDR) and disease relapse are challenging clinical problems in the treatment of leukaemia. Relapsed disease is frequently refractory to chemotherapy and exhibits multiple drug resistance. Therefore, it is important to identify the mechanism by which cancer cells develop resistance. In this study, we used microRNA (miRNA) microarray and qRT-PCR approaches to investigate the expression of miRNAs in three leukaemia cell lines with different degrees of resistance to doxorubicin (DOX) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
136
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(152 citation statements)
references
References 41 publications
12
136
1
3
Order By: Relevance
“…129 Direct regulation of MDR-1 has also been described for miR-331-5p (with the description of a putative miR-331-5p binding site) in resistant K562=DOX leukemia cells. 130 In this study, an inverse correlation between MDR-1 expression and miR-331-5p levels was shown. Furthermore, miR-331-5p overexpression was shown to increase the sensitivity of resistant K562=DOX cells to doxorubicin, through the inhibition of MDR-1 gene expression.…”
Section: Mirs Acting At the Post-transcriptional Level -Direct Regulasupporting
confidence: 53%
See 1 more Smart Citation
“…129 Direct regulation of MDR-1 has also been described for miR-331-5p (with the description of a putative miR-331-5p binding site) in resistant K562=DOX leukemia cells. 130 In this study, an inverse correlation between MDR-1 expression and miR-331-5p levels was shown. Furthermore, miR-331-5p overexpression was shown to increase the sensitivity of resistant K562=DOX cells to doxorubicin, through the inhibition of MDR-1 gene expression.…”
Section: Mirs Acting At the Post-transcriptional Level -Direct Regulasupporting
confidence: 53%
“…130 miR-27a expression was shown to inversely correlate with MDR-1 expression and to increase cell sensitivity to doxorubicin. 130 miRs acting at the post-transcriptional level-possible indirect regulation Several miRs have been described as "indirect regulators" of P-gp, by targeting other mRNAs, which code for intermediate proteins or transcription factors involved in MDR-1 gene activation 128 (Fig. 2 and Table 2).…”
Section: Mirs Acting At the Post-transcriptional Level -Direct Regulamentioning
confidence: 99%
“…36,37 MDR1 is also regulated at RNA level by micro RNAs (miR) such as miR-145, miR-27a and miR-331-5p that bind directly the 3ʹUTR of ABCB1 mRNA to decrease MDR1 expression. 38,39 Some other miR (miR-137) indirectly decrease MDR1 expression by targeting the YB-1 transcription factor that upregulates MDR1 expression by fixation on ABCB1 promoter. 40,41 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the GO functional annotation analysis was performed and found that the four genes were annotated with drug responses related GO terms (Table S6), such as cell cycle, apoptotic process, and DNA damage response. In the STAD DRCEs, four lncRNA, RP11‐473O4.3, LINC01184, LINC00641, and ENSG00000248175, competed for binding to miR‐331, miR‐335, and miR‐106b, which are known to be associated with chemotherapy resistance (Feng et al ., 2011; Kim et al ., 2015; Xia et al ., 2008), thereby regulating their target genes. Consequently, the six DRCEs, hsa‐miR‐335_KLF8_LINC00641, hsa‐miR‐106b_APC_ENSG00000248175, hsa‐miR‐106b_APC_LINC01184, hsa‐miR‐106b_CCND2_ENSG00000248175, hsa‐miR‐331_ATRX_ENSG00000248175, and hsa‐miR‐331_ATRX_RP11‐473O4.3, may affect 5‐FU drug responses (Fig.…”
Section: Resultsmentioning
confidence: 99%